Pengaruh Hasil Deres Getah Pinus (Pinus merkusii Jung. et de Vriese) Terhadap Tingkat Pendapatan Petani Di Kabupaten Gayo Lues - Pohan, Andi Fauzan R; Jamilah, Maryam; Nurhasanah; Muslih, Ali M.; Siregar, Astri Winda; Misdi; Handayati, Triaty; Hanafi, Ilham (Jurnal Hutan dan Masyarakat, 2024)
There are two types of forest products used by the community, namely wood forest products (HHK) and non-timber forest products (HHBK). Most people use wood forest products because they have a very good selling price. In general, there are three uses for wood, namely: as a basic material for making pulp, building materials and craft materials. Various non-timber forest products also make a big contribution to human life, including: rattan, bamboo, sago, agarwood, pine resin, resin, eucalyptus oil, honey and so on. Pine is one of the Non-Timber Forest Products (NTFPs) which produces wood and sap. The sap from pine trees is in the form of a resinous acid liquid which can be further processed into gondorukem and turpentine which are useful in supporting the cosmetics, medicine and food industries. Pine resin is the result of tapping pine trees. Currently, many people are interested in pine sap tapping activities, including in Tetingi Village. Indirectly, this can be used as a source of income for communities around the forest area. This research aims to find out the level of income of the people in Tetingi Village, Pantan Weather District, Gayo Lues Regency and to find out how much Pine Sap contributes to the income of the people of Tetingi Village, Pantan Weather District, Gayo Lues Regency. The population in the research data collection was 25 pine sap tappers as respondents who carried out observations and direct interviews using a questionnaire which was taken in its entirety. The data analysis used in this research is qualitative and quantitative analysis. The results of this research are that the income of pine sap tappers in Tetingi Village is IDR 85,416,200/year with the cost of pine sap tapping being IDR 6,240,110/year, resulting in a profit of IDR 81,153,450/year which is able to increase the income of the community in Tetingi Village. The average income of pine sap tappers in Tetingi Village is IDR 77,734,580/year, income from other sectors is IDR 60,721,632/year and the average total income of tappers is IDR 139,512,314/year, so that pine sap tapping contributes 61,25